Personnel : the management of people at work - Beach, Dale S. (New York : Macmillan Publishing Co.; London : Collier Macmillan Publishers, 1975)
This book has been designed for use in personnel management course, human resources management, applied organizational behavior, and human relations in college, university and business administration program for management, industrial relations, and public administration courses. This third edition includes new developments that have emerged and become important since publication of the second edition. Two entirely new chapters- Chapter 2; work, alienation, and leisure, and Chapter 16; organization development have been added.
Includes bibliographical references and index.
ne 12/07/2018
Loans
Keywords: Personnel management